PENINGKATAN KUALITAS PELAYANAN PELANGGAN MELALUI SISTEM ADUAN BERBASIS WEB - Nova Briyan Haidar; Noor Latifah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
: Customer service quality is a crucial factor for the sustainability of service-based companies, including CV. Selaras Abadi Network. One of the main challenges faced by the partner was the manual handling of customer complaints, which resulted in unstructured records, slow response times, and limited monitoring capabilities. This community service activity aimed to improve customer service quality through the implementation of a web-based complaint system. The implementation method consisted of partner needs analysis, system design, web-based system development, functional testing, as well as training and assistance for system users. The results of this activity indicate that the web-based complaint system was able to streamline the complaint recording and handling process, reduce administrative errors, and enhance service transparency and efficiency. Furthermore, the training activities helped partners operate the system independently. Overall, the implementation of a web-based complaint system proved to be an effective solution for supporting improved customer service quality at CV. Selaras Abadi Network.